PENGARUH PERENCANAAN PRODUKSI DAN STANDAR KUALITAS PRODUK TERHADAP KINERJA OPERASIONAL YANG DIMODERASI OLEH SOP - Fabiyola, Rizcha Oktanza; Widayanti, Sri; Rizkiyah, Noor (Lambung Mangkurat University-Indonesia, 2025)
This study aims to analyze the effect of production planning and product quality standards on operational performance moderated by SOP in Kupang Eucalyptus Oil Agroindustry. The data used in this study are primary data from the results of a questionnaire of 32 Kupang Eucalyptus Oil Agroindustry workers. Sampling was carried out using the census sampling method. The analysis method used in this research is descriptive analysis and Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results showed: (1) production planning does not significantly affect operational performance (2) product quality standards do not significantly affect operational performance (3) SOP significantly affect operational performance (4) production planning has a significant effect on operational performance moderated by SOP (5) product quality standards have a significant effect on operational performance moderated by SOP.